2022
DOI: 10.3389/fonc.2022.827199
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil as a biomarker for diagnosis, prediction, and prognosis evaluation of severe checkpoint inhibitor pneumonitis

Abstract: IntroductionCheckpoint inhibitor pneumonitis (CIP) is a common serious adverse event caused by immune checkpoint inhibitors (ICIs), and severe CIP can be life-threatening. We aimed to investigate the role of peripheral blood cells in diagnosis, prediction, and prognosis evaluation for all and severe CIP.Materials and methodsPatients with lung cancer receiving ICIs were enrolled in this retrospective study. Baseline was defined as the time of ICI initiation, endpoint was defined as the time of clinical diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Pavan et al found that elevated neutrophil-to-lymphocyte ratio (NLR) and platelet-tolymphocyte ratio (PLR) might be associated with the occurrence, severity, and subsequent prognosis of iRAEs (37). In another study, researchers found that the decrease in eosinophils was closely correlated with the CIP, especially for the high grades CIP (38). Importantly, the ratio of the percentage of eosinophils to the percentage of eosinophils at the onset of CIP is an essential marker for distinguishing CIP from pneumonia caused by bacterial infection and cancer progression (39).…”
Section: Serologic Markers Testingmentioning
confidence: 98%
“…Pavan et al found that elevated neutrophil-to-lymphocyte ratio (NLR) and platelet-tolymphocyte ratio (PLR) might be associated with the occurrence, severity, and subsequent prognosis of iRAEs (37). In another study, researchers found that the decrease in eosinophils was closely correlated with the CIP, especially for the high grades CIP (38). Importantly, the ratio of the percentage of eosinophils to the percentage of eosinophils at the onset of CIP is an essential marker for distinguishing CIP from pneumonia caused by bacterial infection and cancer progression (39).…”
Section: Serologic Markers Testingmentioning
confidence: 98%
“…Patients with IAP had low eosinophil percentages at endpoint (Eend)/ baseline (E bas ) values (p = 0.001), especially for severe IAP (p = 0.036). In addition, E end /E bas values performed well in the diagnosis of severe IAP (AUC:0.800, p<0.001), indicating that eosinophil percentage correlates with the diagnosis, prediction and prognosis of IAP [143]. A meta-analysis of 17 RCTs with 2758 patients revealed that individuals with NSCLC and interstitial lung disease (ILD) had a higher likelihood of developing pneumonia after immunotherapy.…”
Section: Icis-associated Pneumonitismentioning
confidence: 99%
“…Recent studies have demonstrated that eosinophils may be involved in CIP. By analyzing the peripheral blood of 430 lung cancer patients treated with ICIs, Li et al ( 67 ) observed that eosinophils in the CIP group (n=67) differed at the beginning of ICI treatment ( E bas ), diagnosis of CIP ( E end ), and 1 week after CIP diagnosis ( E fol ). The E end / E bas ratio signally decreased and was correlated with the severity of CIP.…”
Section: Pathogenesis Of Cipmentioning
confidence: 99%
“…IL-1β is a critical pro-inflammatory factor, primarily synthesized and secreted by monocytes and macrophages. High levels of IL-1β in the serum can promote acute lung injury and pulmonary fibrosis ( 67 , 81 ). Elevated IL-1β at baseline and early in anti-PD-1 therapy (1-6 weeks after anti-PD-1 therapy) is predictive of irAEs ( 70 ).…”
Section: Pathogenesis Of Cipmentioning
confidence: 99%